Membranes based on polyacrylamide coatings on metallic meshes prepared by a two-steps redox polymerization. Performance for oil-water separation and biofouling effects - Cabrera, Jorge Nicolás (2020)
Superhydrophilic oil-water separation membranes were prepared based on chemical (non-photoinduced) polymerization of acrylamide on metal meshes. Membranes were characterized by surface morphological analysis (SEM and AFM), determination of contact angles of water and oil drops, measurement of water flow through the membranes, analysis of dissolved organic in filtered wateroil systems, critical intrusion pressure of oil and surface coverage by bacterial biofilms. The main characteristics of the membranes were studied as function of coverage with polyacrylamide (PAM). The membranes presented efficiencies larger than 99% for toluene-water separation and lifetimes of several months. The intrusion pressure (0.25-1.25 kPa) and water flow (10-300 Lm-2s -1) varied depending on PAM coverage. A mathematical model was implemented for predicting the water flow as function of hydrogel coverage. The results indicate there is a degree of compromise between three factors that are related to the amount of PAM coating: avoiding biofouling (which can block the flow, induce corrosion, etc.), maintaining an important flow of water and sustaining a given intrusion pressure of oil on the membranes.